A selective agraphia of Kana - K. Abe; R. Yokoyama (Behavioural Neurology)
We report a patient who developed selective Kana (phonogram) agraphia following an infarct in the left middle frontal gyrus known as Exner's area. He had well-preserved ability for comprehension, reading, and writing Kanji (ideogram). Kana errors consisted of substitution with another letter while the number of target words was well preserved. It is suggested that a dominant middle frontal gyrus lesion can result in agraphia.